A low profile polarization reconfigurable dipole antenna using tunable electromagnetic band‐gap surface. Issue 6 (June 2014) - Yi, Guangwei; Huang, Cheng; Ma, Xiaoliang; Pan, Wenbo; Luo, Xiangang
ABSTRACT In this article, we present a low profile polarization reconfigurable dipole antenna using a tunable electromagnetic band‐gap (EBG) structure as ground plane. The EBG structure can be dynamically modulated by tuning the loaded PIN diodes through bias voltage circuit. The EBG‐based antenna is fabricated and measured. Experimental results show that the tunable EBG structure can make the dipole antenna work at four states. For the state 1 and state 2, the emitted waves with left‐hand and right‐hand circular polarization are produced at 4.6 GHz, and the axial ratio is 1.2 and 0.3 dB, respectively. For the state 3 and state 4, the dipole antenna radiates the linearly polarized waves with the gains of about 6 dB at 4.6 and 4.25 GHz, respectively. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1281–285, 2014